KATA KERJA BANTU DALAM FILM THE KINGâ€™S SPEECH - Worotitjan, Aprilia Kezia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œAuxiliary Verb in Film The Kingâ€™s Speechâ€ is an attempt to analyze and describe the auxiliary verbs in the film The Kingâ€™s Speech. The aim of this research is to identify and identify the form and meaning of the auxiliary verbs used in the film. The method used in this research is descriptive and the theory using Hudsonâ€™s concept. The result shows that auxiliary verb can be divided into: (a) primary auxiliaries and (b) modal auxiliaries. Primary auxiliaries are be (am, is, are, was, and were) do (do, does, did), and have (have, has, had). Modals auxiliaries are can, could, may, might, will, would, shall, should, must, be to, used to, need. Primary auxiliaries has no intrinsic meaning it serves purely grammatical function. The meaning of modals auxiliaries in the film The Kingâ€™s Speech are: Can means ability, hesitation, permission, and suggestion. Could means ability, possibility, permission, suggestion, and request. May means request and possibility. Might means possibility and permission. Will means willingness, prediction, intention, and request. Would means willingness, certainty, intention , and offering. Shall means request,Â and willness. Should means suggestion, obligation, possibility, necessity. Must means necessity, suggestion, possibility, obligation, and request. Be to means wish. Used to means custom. Need means unnecessary. —————————————————————- Keywords: Auxiliary verb, English, The Kingâ€™s Speech